Effect of Digital Health on Mobilization in Post-Operative Fracture Patients: A Systematic Review - Baiq Rista Ananta Pratiwi; Ninuk Dian Kurniawati; Ika Nur Pratiwi (GLOBAL HEALTH SCIENCE GROUP, 2025)
Post-operative rehabilitation for fracture patients is crucial in restoring mobility and preventing complications such as muscle atrophy, joint stiffness, and deep vein thrombosis. However, traditional rehabilitation methods often face significant barriers, including limited accessibility, high costs, and low patient adherence. These challenges highlight the need for innovative approaches to enhance rehabilitation outcomes. Digital health interventions (DHIs), such as mobile applications, telerehabilitation, and IoT (Internet of Things) devices, have emerged as promising solutions. By providing remote monitoring, real-time feedback, and personalized care, DHIs address many of the limitations of traditional rehabilitation methods and offer opportunities to improve recovery outcomes. Objective: This systematic review aims to evaluate the effectiveness of digital health interventions (DHIs) in improving mobilization and overall recovery for post-operative fracture patients. Methods: A comprehensive search was conducted across PubMed, Scopus, ScienceDirect, Web of Science, and ProQuest for studies published between 2019 and 2024. Keywords included